Re-Evaluating the Transplant Glomerulopathy Lesion—Beyond Donor-Specific Antibodies - Arun Chutani; Daniel Guevara-Pineda; Gabriel B. Lerner; Madhav C. Menon (Transplant International)
There have been significant advances in short-term outcomes in renal transplantation. However, longer-term graft survival has improved only minimally. After the first post-transplant year, it has been estimated that chronic allograft damage is responsible for 5% of graft loss per year. Transplant glomerulopathy (TG), a unique morphologic lesion, is reported to accompany progressive chronic allograft dysfunction in many cases. While not constituting a specific etiologic diagnosis, TG is primarily considered as a histologic manifestation of ongoing allo-immune damage from donor-specific anti-HLA alloantibodies (DSA). In this review article, we re-evaluate the existing literature on TG, with particular emphasis on the role of non-HLA-antibodies and complement-mediated injury, cell-mediated immune mechanisms, and early podocyte stress in the pathogenesis of Transplant Glomerulopathy.